Estratégia para competitividade em cooperativas de crédito: o caso da Credivertentes - Silva Filho, Gil Teixeira da (2001)
The credit cooperativism is one ofthe segments ofthe cooperativism that has developed most in the last 20 years. However, this movement has been passing through structural problems that are directly related to management problems. This study has as objective to make a diagnosis in a rural credit cooperative ofMinas Gerais and, from that, suggest competitive strategies to the organization in its actingáreas. For that, the historical development ofthe credit cooperativism, its insertion in the National Financial System, goingthrough the management and evaluation of financial organizations and getting to the strategic planning focus, present in enterprise strategy studies, were used. As a theoretic/analytical model it was used the Transaction Costs Economy approach present in New Institutional Economy researches. For the economical analysis it was used the Economic Management model (GECON) developed by researchers of the University of São Paulo (USP). It was concluded that the National Financial System is one ofthe most mled economic segments ofthe countryand that the credit cooperativism is extremely influenced by the institutional environment in which it is inserted. The evaluation ofthe performance of the cooperative that was studied proved to be an instrument ofgreat importance, especíally as a tool for the decision making. Finally, suggestions were presented so that the cooperative can act in a way to become competitive in its acting áreas.